1964
DOI: 10.1172/jci105043
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Clearance and Estimated Hepatic Blood Flow during Mild to Maximal Exercise in Upright Man *

Abstract: Krogh in 1912 (1) postulated the necessity for a large capacity venous reservoir capable of quickly delivering an autotransfusion of blood into the right heart during exercise, particularly in upright man, where Krogh felt venous return may at times be inadequate. Bock and co-workers (2) in their classical work reasoned that increased blood flow to working muscle, related in part to local vasodilation, must be partially effected by decreased splanchnic blood flow. Since the splanchnic region receives 20 to 25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
193
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(206 citation statements)
references
References 24 publications
12
193
1
Order By: Relevance
“…Hepato-splanchnic blood flow was estimated from measurements of peripheral ]ndocyanine green clearance [10]. After 25 rain of supine rest, 3 ml blood were drawn from the right arm into heparinised tubes for preparation of plasma blanks.…”
Section: Me~o~mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepato-splanchnic blood flow was estimated from measurements of peripheral ]ndocyanine green clearance [10]. After 25 rain of supine rest, 3 ml blood were drawn from the right arm into heparinised tubes for preparation of plasma blanks.…”
Section: Me~o~mentioning
confidence: 99%
“…Spectrophotometric analysis of urine (collected after the experiment) from group 3 patients with added human serum albumin showed that Indocyanine green was not lost in the urine. The plasma Indocyanine green fractional disappearance rate (k) was determined from the regression line for the log plasma concentrations versus time, calculated by the least squares method [10]. Plasma clearance, which varies in parallel with hepatic blood flow, was then calculated as k x plasma volume.…”
Section: Me~o~mentioning
confidence: 99%
“…Blood flow to liver significantly reduces when an individual undertakes physical exercise in upright posture [7][8][9][10] This was the basis of popular hypothesis of yesterday. that exertion may be harmful to patients of AVH [11].…”
Section: Discussionmentioning
confidence: 99%
“…the lower body. Lower body exercise training has been demonstrated to lessen the decrease in blood flow to splanchnic, renal and cutaneous areas at a given power output (Ho et al, 1997;Rowell et al, 1964;1965) whereas blood flow to muscle remains unaffected (Stolwijik ,1997). Since upper body exercise affects splanchnic, renal and cutaneous blood flow (Ahlborg et al, 1975) it is possible that upper body training may also influence vasomotor responses in other areas such as calf volume changes during exercise.…”
Section: Introductionmentioning
confidence: 99%